1993
DOI: 10.1159/000116974
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Event-Related Potentials in Patients with Systemic Lupus erythematosus

Abstract: We studied auditory event-related potentials (ERPs) in 17 patients with systemic lupus erythematosus (SLE). Latencies of N100 and P200 components were normal in all patients, whereas the latencies of target P300 and nontarget P300 components were significantly prolonged in SLE patients with and without cognitive dysfunction. The P300 component of ERPs can be applied to evaluate the cognitive aspects of central nervous system manifestations in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
4
2
1
Order By: Relevance
“…There were wide variations in the reported prevalence of neurophysiological abnormality in patients with SLE. In our study, the prevalence of neurophysiological abnormalities (83%) among lupus patients was much more than reported in previous studies [8,9,[29][30][31]. This may be related to the fact that there were more neurophysiological tests in our study compared to other studies and also to the duration of the disease since diagnosis.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…There were wide variations in the reported prevalence of neurophysiological abnormality in patients with SLE. In our study, the prevalence of neurophysiological abnormalities (83%) among lupus patients was much more than reported in previous studies [8,9,[29][30][31]. This may be related to the fact that there were more neurophysiological tests in our study compared to other studies and also to the duration of the disease since diagnosis.…”
Section: Discussioncontrasting
confidence: 58%
“…Paiva et al [10] found P300 responses to be abnormal in 33% of patients with CNS lupus and in 22% of patients with non-CNS lupus. While Ito et al [29] recorded significant prolongation of P300 in lupus patients compared with controls, 6 out of 17 of their patients (35%) had abnormal values. The discrepancy between the incidence of abnormality may be due to the wide range of normality of P300 latency.…”
Section: Discussionmentioning
confidence: 85%
“…Similar abnormalities in the P300 parameters have already been reported in SLE patients, with their frequency ranging from 35% to over 70%. [3][4][5][6] Considering the mainly subcortical localization of CNS lesions in the course of SLE, one could expect more common abnormalities of the N200 component, which is attributed to early, subconscious stimulus processing. Prolonged latency of N200 was less commonly found in our patients than that of the P300 component.…”
Section: Discussionmentioning
confidence: 99%
“…However, ERPs parameters as an electrophysiological index of cognitive function have rarely been investigated in SLE patients. [3][4][5][6] The relationship between different auto-antibodies and NP syndromes in SLE remains a matter under investigation. Some auto-antibodies, such as antiphospholipid, are widely associated with nervous system involvement, while others (e.g., anti-Rib-P and anti-gangliosides) have been the subject of only a few studies and with equivocal results.…”
Section: Introductionmentioning
confidence: 99%
“…La comparación entre grupos, por medio de este potencial ha sido utilizada en diversas situaciones clínicas, con similares interpretaciones respecto a la significación de este hallazgo [23][24][25][26] .…”
Section: Discussionunclassified